Adaptive Learning : Learning Design Training Differentiated AI -based for Elementary School Teachers - Siti Amaliati; Arifatul Ma'ani; Syovinatus Sholicha; Eva Andriani; Muksin Muksin; Ely Fitriani; Machfud Bachtiyar (Tarqabin Nusantara Group, 2025)
This Community Service Program (PkM) aims to enhance the pedagogical capacity of elementary school teachers in Dusun Kepetingan in implementing adaptive and differentiated instruction supported by Artificial Intelligence (AI). The training employed a Participatory Action Research (PAR) framework, comprising conceptual strengthening, analysis of students’ learning needs, and hands-on practice using Quizizz AI for differentiating content, process, and product. Findings indicate substantial improvements in teachers’ ability to design instructional scenarios that are responsive to classroom heterogeneity. Evaluation results show a satisfaction rate of 92%, demonstrating the relevance and effectiveness of the program. This PkM underscores the strategic potential of AI integration in supporting systematic, efficient, and data driven implementation of differentiated learning.